Lymph Drainage of Posttraumatic Edema of Lower Limbs - Ana Carolina Pereira de Godoy; Rodrigo Ocampos Troitino; Maria de Fátima Guerreiro Godoy; José Maria Pereira de Godoy (Case Reports in Orthopedics)
Objective. The present study was aimed at evaluating the use of mechanical and manual lymphatic therapy as a treatment for lymphedema resulting from orthopedic surgery that became painful after an episode of erysipelas. Case Report. A 70-year-old male patient suffered direct trauma resulting in a compound fracture of the tibia and fibula of the left leg. He was treated with an external fixator for four months followed by plaster cast immobilization for three weeks. He presented with fever and paresthesia in the lower left limb that resulted in an episode of erysipelas, and the patient evolved with painful lymphedema. Treatment using the Godoy and Godoy technique was proposed, including manual and mechanical lymphatic therapy. Water displacement volumetry was used to quantify the leg size reduction. Results. After 10 sessions of therapy, the patient presented a significant reduction in the limb volume and remission of symptoms. Conclusions. The method used may be a promising option for the treatment of posttraumatic edemas with pain.